Retrospective Cohort Analysis of Central Line Associated Blood Stream Infection following Introduction of a Central Line Bundle in a Neonatal Intensive Care Unit - Molly Bannatyne; Judith Smith; Malavika Panda; Mohamed E. Abdel-Latif; Tejasvi Chaudhari (International Journal of Pediatrics)
Background. Central Line Associated Bloodstream Infections (CLABSI) constitute a leading cause of morbidity and mortality in neonatal populations. There has been an overwhelming increase in the use of evidence-based care practices, also known as bundles, in the reduction of these infections. In this report, rates of CLABSI and central line utilisation were examined following the introduction of a central line bundle in our Neonatal Intensive Care Unit (NICU) at the Canberra Hospital. Methods. The research undertaken was a retrospective cohort study in which newborn infants admitted to the Canberra Hospital NICU between January 2011 and December 2016 and had a central line inserted were included in the study. Data regarding central line days, bed days, infection rates, and patient demographics were collected before and after the introduction of an intervention bundle. CLABSI rates were calculated per 1,000 central line days for before (2011-2013) and after (2014-2016) the introduction of the bundle. The postintervention period was retrospectively analysed for compliance, with data regarding the completion of maintenance forms and insertion forms collected. Results. Overall, the results showed a significant decrease in CLABSI rates from 8.8 per 1,000 central line days to 4.9 per 1,000 central line days in the intervention period (p<0.001). Central line utilisation ratio (CLUR: ratio of central line days to bed days) was also reduced between pre- and postintervention periods, from 0.177 (4414/25013) to 0.13 (3633/27384; p<0.001). Compliance to insertion forms and maintenance forms was observed to increase within the intervention period. Conclusion. The implementation of a central line bundle was effective in reducing both CLABSI rates and dwell time (CLUR) for central venous catheters.